ASEAN Defence Ministers MeetingPlus: Institutional structure, specific features, and evolution (2010–2022) - K. G. Muratshina (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The Association of Southeast Asian Nations (ASEAN) is one of the key multilateral structures in Asia-Pacific. Throughout its history, the organization has established a system of external partnerships. In 2010, a specific security-related dialogue format has been introduced into this system, — the ASEAN Defence Ministers Meeting-Plus (ADMM-Plus). In order to provide a better understanding of the legal nature of the ADMM-Plus as an international grouping, and to discuss the dynamics of its evolution, as well as the practical results of its work, this paper examines the Meeting’s activities in the recent years (2010 to 2022) and identifies the stages of its institutional development. The author notes that, unlike other similar fora, ADMM-Plus has a strictly limited number of participants. It could seem counterproductive, however, both ASEAN and its dialogue partners keep up to the closed nature of the grouping, beware of the potential contradictionsincaseofitsexpansion.Theauthoralsoconductsthediscourse analysis of the ADMM-Plus documents and member statements, highlighting +-the views of the participants and identifying the current international positioning of the forum. In conclusion, the paper emphasizes that, in the context of the fundamental changes in the world order, ASEAN has proven its ability to control the sensitive agenda of the ADMM-Plus, and stays committed to its principles of multi-faceted policy. At the same time, the affinity of Russian and ASEAN approaches towards the development of Asia-Pacific is displayed. While other dialogue partners, primarily the United States and China, are pressurising ASEAN in order to ‘win over’ the Southeast Asian countries to their side, Russia consistently promotes an equal, practice-oriented dialogue, and adheres to the principles of non-interference in internal affairs and in local conflicts. The author concludes that, in spite of the low-profile practical achievements of the ADMM-Plus, the Meeting remains suitable for all its participants, as the main effect of its activity represents the maintenance of contacts and negotiations in the defence area in the face of the new regional security challenges.